COMMUNICATIVE LANGUAGE TEACHING IN ESL CLASSES - Ochilboyeva Iroda Alisherovna; Qudratova Dilnora Ravshanovna (International Journal of Innovations in Engineering Research and Technology, 2021)
This article states different methods, emphasizing the Communicative Language Teaching (CLT) in ESL classes. Furthermore, we studied the way; students learn a foreign language and also its impact on a class motivation. In our research initially it is studied literature regarding the Method of Communication and its advantages compared to other methods as part of behavior, cognitive or human theories.